The microRNA‐146a/b attenuates acute small‐for‐size liver graft injury in rats. (17th September 2014) - Jiang, Weiwei; Ni, Qingfeng; Tan, Longwei; Kong, Liangliang; Lu, Yeting; Xu, Xiaoqun; Kong, Lianbao
Abstract Background & Aims A critical role of the Toll‐like receptor (TLR)‐4 and its downstream mediators in the pathogenesis of small‐for‐size liver graft injury has been documented. Recently, the microRNA‐146 (miR‐146) was identified as a potent negative regulator of the TLR4 signalling pathway. In this study, the role of miR‐146a and miR‐146b in the attenuation of TLR‐4 signalling and small‐for‐size liver graft injury was investigated. Methods The expression levels of miR‐146a and miR‐146b during small‐for‐size liver graft injury were studied in vivo. In addition, the effects of miR‐146a and miR‐146b on the expression of IRAK1 and TRAF6 in the rat macrophage cell line NR8383 and rat liver kupffer cells were studied in vitro. The in vivo effect of miR‐146a and miR‐146b on small‐for‐size liver graft injury was studied by the tail vein injection of miR‐146a mimics and miR‐146b mimics. Results The levels of miR‐146a and miR‐146b decreased with a small‐for‐size liver graft. MiR‐146a and miR‐146b inhibited IRAK1 and TRAF6 expression by binding to the 3′UTR of IRAK1 or TRAF6, respectively, in the rat macrophage cell line NR8383. The administration of miR‐146a mimics and miR‐146b mimics prevented liver graft injury in small‐for‐size liver graft injury via the inactivation of IRAK1 and TRAF6 in vivo. Conclusions miR‐146a and miR‐146b prevent liver injury in small‐for‐size liver graft injury via the inactivation of IRAK1 and TRAF6.